The British nuclear experience : the roles of beliefs, culture and identity - Baylis, John, 1946-; Stoddart, Kristan (Oxford University Press, 2015)
Based on a detailed analysis of archives and high level interviews this book looks at the role of beliefs, culture and identity in the making of British nuclear policy from 1945 through to the present day.